Exploring augmentation of meaning through intersemiotic complementarity in children comic book series - Nur Annisa Haris; Yusnita Febrianti; Nurenzia Yannuar (Universitas Pendidikan Indonesia, 2023)
Comic books are taking a new turn as a medium of learning. The combination of modes of visual and verbal in comics is a rich source of meanings. They are arguably one of the contributors to why comic books are considered as a form of reading materials for the purpose of language learning. With this regard, the present study is looking into a comic book series targeted for young readers, entitled ‘Little Dim Sum Warriors’. The overall aim of the study is to comprehend how the readers are likely to learn language with the comic. More specifically, the study addresses the details of the verbal-visual relation in LDSW and the prediction on how readers might be able to perceive the meaning-making process in LDSW. In doing so, the study analyzes the first two installments of the series in terms of the relationships between the verbal texts and visual images in terms of the ideational meanings. Data analysis is facilitated primarily using Royce’s (1998) framework of ideational Intersemiotic Complementarity to map out and categorize any instances of visual-verbal relation in the data in terms of the instances of repetition, synonymy, antonymy, hyponymy, meronymy, and collocation. Through the analysis, the study found that the verbal-visual relations mostly fall into the categories of repetition and collocation, which further indicate that the repeated meaning in both verbal and visual aspects are found effective in learning language. Other relations, however, such as those that appeared as anonymy or synonymy, might require the attendance of teachers or parents to create a discussion with the young readers regarding the meaning-making process. The results of the study also implied some hints on how reading activities between parents and children may be conducted.